An Algorithm for Reducibility of 3-Arrangements (Communications in Mathematical Research, 2021)
We consider a central hyperplane arrangement in a three-dimensionalvector space. The definition of characteristic form to a hyperplane arrangement isgiven and we could make use of characteristic form to judge the reducibility of thisarrangement. In addition, the relationship between the reducibility and freeness of ahyperplane arrangement is given.